1982
DOI: 10.1073/pnas.79.11.3433
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of elongation factor 1 alpha from the fungus Mucor.

Abstract: A basic protein from the dimorphic fungus Mucor racemosus, found to be highly methylated, is shown to be protein synthesis elongation factor la. This protein is the most abundant protein in hyphal cells but is less abundant in yeast cells. It is posttranslationally methylated with the formation of mono-, di-, and trimethyllysine at as many as 16 sites. Nearly 20% of the 44 lysine residues of elongation factor la from mycelia are modified while those from sporangiospores are virtually unmethylated.Mucor racemos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 41 publications
(17 reference statements)
2
34
0
Order By: Relevance
“…A constant, high level of EF-la mRNA during the time that activity was changing raised the question of whether the EF-la protein was being synthesized at similarly constant levels. This question was approached by germinating spores in [35S]methionine and determining the relative amount of EF-la protein from its unique position in a two-dimensional polyacrylamide gel (9). We found that the amount of EF-la protein, measured as a proportion of total cellular protein, changed little during spore germination (Table 1) and did not reflect the change in specific activity of the factor.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…A constant, high level of EF-la mRNA during the time that activity was changing raised the question of whether the EF-la protein was being synthesized at similarly constant levels. This question was approached by germinating spores in [35S]methionine and determining the relative amount of EF-la protein from its unique position in a two-dimensional polyacrylamide gel (9). We found that the amount of EF-la protein, measured as a proportion of total cellular protein, changed little during spore germination (Table 1) and did not reflect the change in specific activity of the factor.…”
Section: Resultsmentioning
confidence: 96%
“…These alternative forms of growth, as well as the process of spore germination, are accompanied by differences in the translational system. Among these are differences in the rate of peptide bond formation (18,19), the extent of phosphorylation of ribosomal protein S-6 (11,12), and the methylation of the elongation factor EF-la (9). In the latter case, we have found that of the 44 lysine residues, 8 or 9 are methylated when the organism grows in the mycelial form (9).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Methylation of lysine residues is another posttranslational modification of EF-1 alpha [Hiatt et al, 1982;Coppard et al, 1983;Fonzi et al, 1985;Sherman and Syphered, 19891 and it has been correlated with cell differentiation and increases in protein synthesis [Coppard et al, 1983;Fonzi et al, 1985;Sherman and Syphered, 19891. In this regard it is interesting that the sequence around lysine 309 in ABP-50, + G T P~ f + G T P~ when GTP was added to ABP-50 for 10 min prior to incubation with F-actin; +GTPh, when ABP-50 was pre-incubated with F-actin for 10 min prior to the addition of GTP.…”
Section: Possible Mechanisms For the Regulation Of The Cytoskeletal Imentioning
confidence: 99%
“…EF-l (\' III fungus Mucor racell/OSIiS has been previously shown to be post tnlll! '>latlOnall y modi lied hy \11ethylation of Iysiue rcsidues (Hiatt et al, 1982).…”
mentioning
confidence: 99%